ASUHAN KEBIDANAN IBU BERSALIN DENGAN PERDARAHAN POST PARTUM PADA NY. “N” DI BPM BIDAN LILIS NURHASANAH, S.ST.KEB, SKM TAHUN 2019 - Ika Apriyanti; Rizka Youliawaty (Journal Of Applied Health Research And Development, 2019)
Post partum hemorrhage is bleeding that exceeds 500 ml after the baby is born. In general, if there is bleeding that is more than normal, especially if it has caused changes in vital signs (such as decreased consciousness, pale, unsteady, cold sweats, shortness of breath, and tension <90 mmHg and pulse> 100 / minute), then treatment must be done immediately. According to USAID Jalin Banten in 2016 there were 240 cases of maternal deaths in Banten and 38% of them were caused by bleeding. This study was conducted so that students were able to provide midwifery care for postpartum hemorrhage cases in Ny. "N" at PMB Lilis Nurhasanah, S.ST. Keb, SKM. The method used in writing this case study is a qualitative method in which data collection methods in a case study can be done by interview using the format of maternity assessment, maternal observation, and medical records in the form of patient status. After the assessment and examination, it was found that in Ny. "N" occurs post partum bleeding. The care given to Mrs. "N" is to put up a 500 ml RL drip oxytocin 20 IU 60 tpm infusion, explore the uterine cavity, inject IM methergin in 1/3 of the outer thigh of the mother, give misotab (misoprostol 0.2 mg) 3 role tabs, perform check the hemoglobin level in the mother's blood, and observe the amount of bleeding. It is hoped that this case study can be a reference in maintaining the quality of midwifery services, especially in providing comprehensive midwifery care to women with post partum hemorrhage